Efficacy and safety of edaravone dexborneol in acute ischemic stroke: systematic review and meta-analysis - Moghib, Khaled; Hefnawy, Mahmoud Tarek; Moawad, Shehab M.; Salomon, Izere; Hamdi, Ahmed; Uwishema, Olivier; Meshref, Mostafa (Frontiers in Neurology, 2025)
BackgroundEdaravone dexborneol represents a novel neuroprotective agent utilized in the treatment of acute ischemic stroke (AIS). Preliminary studies indicate that this combination exhibits enhanced therapeutic effects when compared to the use of edaravone alone. The objective of this study was to assess the efficacy and safety of edaravone dexborneol in the management of AIS.MethodThis systematic review and meta-analysis were conducted following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement guidelines. A comprehensive search of the PubMed, Cochrane Central, Scopus, and Web of Science databases was performed on December 30, 2024. Subsequently, we screened articles for eligibility, relevant data were extracted, and the risk of bias was assessed utilizing the Cochrane Collaboration Tool 2. The primary outcome evaluated was the efficacy of edaravone dexborneol in the management of AIS, as measured by the National Institutes of Health Stroke Scale (NIHSS) and the modified Rankin Scale (mRS). Secondary outcomes encompassed improvements in activities of daily living (ADL), reductions in post-stroke depression, inflammation, and hemorrhagic transformation, as well as enhancements in cognitive function, as indicated by Montreal Cognitive Assessment (MoCA) scores. Extracted data from pertinent Randomized Controlled Trials (RCTs) were analyzed using R programming for Windows. All procedures outlined in this study were pre-specified, and the protocol has been registered with PROSPERO under the unique identifier CRD42024626320.ResultsA total of six randomized controlled trials (RCTs) and one cohort study, all conducted in China and involving 2,942 patients with ischemic stroke (65.6% male), were included. Treatment regimens consisted of intravenous or sublingual edaravone dexborneol administered for 10–14 days. The pooled analysis of functional outcomes at 90 days, based on five studies, demonstrated a significant benefit, with a 39.5% higher likelihood of achieving favorable mRS scores (OR = 1.40, 95% CI: 1.18–1.65, p = 0.0001), without evidence of heterogeneity (I2 = 0%). In contrast, pooled analysis of NIHSS outcomes across seven studies using a random-effects model was not significant (SMD = −0.113, 95% CI: −0.333 to 0.107, p = 0.314), with substantial heterogeneity (I2 = 72.7%). However, under the common-effect model, a small but statistically significant benefit was observed (SMD = −0.083, 95% CI: −0.159 to −0.008, p = 0.030). Sensitivity analyses indicated that several studies (Fu 2024, Hu 2023, Xu 2019, Xu 2024) attenuated the pooled effect, while exclusion of Li 2024 and Hu 2023 reduced heterogeneity to 40.7% but resulted in only borderline significance. Secondary endpoints consistently demonstrated favorable effects, including improved activities of daily living, enhanced cognitive function (MoCA scores), and reduced rates of post-stroke depression, inflammation, and hemorrhagic transformation. Safety analyses revealed that adverse events were generally mild and comparable to controls, with some evidence suggesting a reduction in serious complications such as hemorrhagic transformation.ConclusionEdaravone dexborneol exhibits considerable potential as a neuroprotective agent in the context of AIS, providing both functional and cognitive advantages, alongside a favorable safety profile. The promising efficacy of this compound underscores the necessity for further comprehensive global studies aimed at optimizing its application and enhancing its relevance across diverse populations.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024626320.